Mapping a measure of physical ability for persons with long-term musculoskeletal pain to the ICF and ICF Core Sets. (30th July 2018) - Fresk, Magdalena; Brodin, Nina; Grooten, Wim J; Joseph, Conran; Kiessling, Anna
Abstract: Background: Test Instrument for Profile of Physical Ability (TIPPA) is used in the Swedish sickness certification process for patients with long-term musculoskeletal pain. The aim was to explore the content of TIPPA in the context of work-ability assessments. Methods: The full protocol of TIPPA was linked to the in relation to the International Classification of Functioning, Disability and Health (ICF) and evaluated in relation to the ICF Core Sets for Chronic Widespread Pain (CWP). Results: Twenty-two unique meaningful concepts were identified in TIPPA. Eighteen of those could be linked to ICF, yielding 27 third-level ICF-categories. Ten of these categories fitted the domains of 'body function', 16 were 'activity and participation', while one was related to 'environmental factors'. Perspective and aim varied between the parts of the test. When assessed against Brief ICF Core Set for CWP, TIPPA covered three of nine 'body function' categories and 2 out of 10 'activity and participation' categories. The coverage of the subgroup 'activity' was two out of five. TIPPA did not cover three categories, i.e. 'd175 solving problems', 'd230 carrying out daily routine' and 'd240 handling stress and other psychological demands', in the subgroup of 'activity'. Conclusions: TIPPA could be a useful measure for the assessment of physical ability. However, additional condition-specific items/measures are required to obtain full coverage of core aspects of functioning and disability in a comprehensive work-ability assessment for patients with long-term musculoskeletal pain.